Tantangan Pembelajaran Bahasa Arab Di Era Society 5.0: Analisis Pembelajaran Bahasa Arab Berbasis Aplikasi Interaktif - Husnaini Jamil; Nur Agung (IAIN Madura, 2022)
The Revolutionary Era 4.0, which has just been rolled out, has been replaced by the presence of the Society 5.0 era which directs people to utilize technology in every activity, including in the field of education. Arabic as a foreign language taught in various Indonesian educational institutions is also trying to keep up with the times. One of the breakthroughs made by educators is to convert and adapt Arabic teaching materials which were in the form of books, modules, and audio into interactive teaching materials designed with the latest applications. This brings out new ideas for the progress of learning Arabic, so that various difficulties experienced so far can be overcome properly. This study aims to identify and describe the challenges faced by Arabic language activists in the era of society 5.0 based on the use of interactive applications to make Arabic learning videos. The research was carried out with a descriptive quantitative approach to explain the results of research in various educational institutions in Bone Regency. The result of this research is that the teachers must have special skills to optimize the use of technology in the learning process, so that students can absorb more of the materials. It can be run by operating video editing applications such as Kine Master, Plotagon, PowerPoint, and others